Antibacterial activity of some mangrove species in Xuan Thuy national park, Nam Dinh, Vietnam - Linh, Tran My; Giang, Vu Huong; Lien, Le Quynh; Van, Nguyen Tuong; Ban, Ninh Khac; Minh, Chau Van (Academia Journal of Biology, 2013)
Possessing more than 3,000 km coastal lines, Vietnam has several mangrove forests which are potential sources of natural products with pharmaceutical properties. In order to investigate the applications of mangrove forests in Vietnam, nine mangrove plants including Kandelia obovata, Pluchea pteropoda Hemsl., Aegiceras corniculatum (L.) Blanco, Lumnitzera racemosa Wild., Sonneratia caseolaris (L.) Engl., Sonneratia apetala Buch. Ham, Bruguiera gymnorrhiza (L.) Lam, Rhizophora stylosa Griff. and Avicennia marina (Forsk.) Vierh. were collected in Xuan Thuy National Park, Nam Dinh province, Vietnam. Methanol extracts from barks and leaves of these species were used to evaluate antibacterial activity against 4 control bacteria Escherichia coli ATCC®25922™*; Staphylococcus aureus ATCC®25923™; Proteus mirabilis ATCC®29245™ and Proteus vulgaris ATCC®33420™ via the agar well diffusion method. All of methanol extracts from nine mangrove plant species collected in Xuan Thuy National Park inhibited the growth of tested pathogenic bacterial strains. Lumnitzera racemosa Wild., Sonneratia caseolaris (L.) Engl. and Sonneratia apetala Buch. Ham expressed the highest antibacterial activity. Aegiceras corniculatum (L.) Blanco and Avicennia marina (Forsk.) Vierh showed medium activity. Kandelia obovata, Pluchea pteropoda Hemsl., Rhizophora stylosa Griff. and Bruguiera gymnorrhiza (L.) Lam showed the lowest activity.